Antibacterial Effectiveness Test of Sandalwood Leaf Extract (Santalum album) Against Pathogenic Bacteria Escherichia coli and Staphylococcus aureus - Jasmine Kiran Amiroh; Anita Lidesna Shinta Amat; Iswaningsih Iswaningsih; I Made Buddy Setiawan (BIOPENDIX, 2026)
Infectious diseases are diseases caused by organisms such as bacteria, viruses, fungi or parasites. One of the causes of most infectious diseases comes from bacterial infections, including Escherichia coli and Staphylococcus aureus. Treatment for bacterial infections is generally by administering antibiotics. Treatment using plants containing antibacterials is an alternative that is being widely studied as an effort to kill bacteria other than the use of antibiotics. One of the plants cultivated and used as a medicinal plant is sandalwood (Santalum album). This research was carried out to evaluate the antibacterial activity of sandalwood leaf extract (Santalum album) against Escherichia coli and Staphylococcus aureus. The research utilized a true experimental framework with a posttest-only control group design, featuring treatment groups consisting of a Ciprofloxacin positive control, a sterile aquadest negative control, and varying concentrations of sandalwood leaf extract (ranging from 3.12% to 100%), each replicated three times against Escherichia coli and Staphylococcus aureus strains. Data analysis used the Kruskal-Wallis statistical test with a 95% degree of confidence. Based on the results of testing the antibacterial potential of sandalwood leaf extract on the growth of Escherichia coli and Staphylococcus aureus bacteria, it was shown that the extract had antibacterial potential. Analysis of the Kruskal-Wallis test showed that p = 0.002 was smaller than α = 0.05, showing there was a significant variation in the mean diameter of the inhibition zones between the different treatment groups. There is an antibacterial effectiveness of sandalwood leaf extract (Santalum album) against Escherichia coli and Staphylococcus aureus bacteria